TRANSFORMATION OF WAR – USE OF CONVENTIONAL MILITARY FORCES AGAINST STATE ACTORS (Годишен зборник на Филозофски факултет - Скопје, 2021)
Immediately after the initial military success of the US military in 2001 and the overthrow of the Taliban regime in Afghanistan, insurgent mujahedeen groups quickly began to form. Mixed insurgent groups formed by the Taliban, Hezbollah and Islamists, the Haganah network, foreign mercenaries, local tribes, and criminal organizations have been pushing hard to overthrow the Afghan government. The efforts of the United States and its coalition partners in dealing with the mujahedeen forces have provided an excellent opportunity to assess what works and what does not work in terms of fighting an asymmetric enemy by conventional means in an unconventional combat environment.The questions on which this research is based are: Why has modern sophisticated military technology and numerous conventional military superiorities failed to deal with the 4GB insurgent groups and failed to meet the expected results in countering threats to stability in Afghanistan? In this scientific paper, we will give an answer to this research question and at the same time, we will try to prove the reasons that led to the change of the essence and the conduct of the war in the XXI century.